Formation process and properties of hydrogen-producing granular sludge in UASB reactor - Yin, Lili; Liu, Shuang; Wang, Mengyi; Ju, Wencong; Wei, Donghui; Li, Wenzhe (International Journal of Agricultural and Biological Engineering, 2018)
The granular sludge of microbial fermentation systems includes various biomass-degrading enzymes and different microflora, which have significant impacts on the degradation of biomass and the stability of the system. An up-flow anaerobic sludge blanket (UASB) reactor was used to grow hydrogen-producing granular sludge. The results showed that the formation of the granular sludge underwent four stages, i.e., flocculation of the sludge, formation of the flocculent sludge, swelling of the flocculent sludge, and formation of the granular sludge. The formed granular sludge mostly had regular spherical and ellipsoidal shapes with a fractal dimension of 2.08±0.4; the settling velocities were 0.84 cm/s to 1.96 cm/s in water, the porosity was 0.67-0.95.The shear sensitivity (Kss) of the granular sludge was 0.1152. The granular sludge had a culture cycle of approximately 70 d and a hydrogen yield of 1.09 mol H2/mol glucose.Keywords: Anaerobic fermentation, UASB reactor, granular sludge, hydrogenDOI: 10.25165/j.ijabe.20181105.4255Citation: Yin L L, Liu S, Wang M Y, Ju W C, Wei D H, Li W Z. Formation process and properties of hydrogen-producing granular sludge in UASB reactor. Int J Agric & Biol Eng, 2018; 11(5): 224–229.